Strain theory, resilience, and far-right extremism: the impact of gender, life experiences and the internet. Issue 1 (2nd January 2022) - Skoczylis, Joshua; Andrews, Sam
ABSTRACT: There has been a notable increase in support for far-right ideologies across the West. The seriousness of this threat has been acknowledged by the UK government which has banned certain far-right groups using terrorism legislation. While criminological theories have been useful in explaining general criminality, they have been under-utilised in explaining extremism and terrorism. Agnew's General Strain Theory, which hypothesises that negative life events increase the chance of a turn to criminality, is explored in this article alongside Control Theory. Based on a survey (N 1, 138) conducted on Facebook in late 2019, we explore how strain and resilience based on participants' gender, economic situations, life events and their use of the internet impacts individuals' far-right extremist attitudes and behaviours. We use regression analysis to investigate the impact that strain and resilience, individuals' gender, economic situations, individual life experiences, and their use of the internet have on their propensity to associate, engage, and support far-right ideologies and linked violence. While strain is not found to be significant, resilience, gender and the use of the internet are.